Agreement between retrospectively assessed health-related quality of life collected 1 week and 12 months post-injury: an observational follow-up study - Haagsma, Juanita (Health Qual Life Outcomes, 2019)
BACKGROUND: Retrospective assessment of pre-injury health-related quality of life (HRQL) is frequently used to measure change from pre- to post-injury HRQL. However, retrospective measurement may be confounded by recall bias. It is assumed that presence of recall bias is influenced by several factors, such as the measurement scale or the instrument that is used, the measurement schedule, and the presence of a substantial health event during the follow up period. This study empirically tests these assumptions by comparing pre-injury EQ-5D summary scores, EQ-5D profiles and visual analogue scale (EQ-VAS) scores of trauma patients, as recorded 1 week and 12 months post-injury, respectively. METHODS: A sample of 5371 adult trauma patients who attended the Emergency Department (ED) followed by hospital admission, received postal questionnaires 1 week (T1) and 12 months (T2) post-injury. The questionnaires contained items on pre-injury health, in terms of EQ-5D3L and EQ-VAS. RESULTS: One thousand one hundred sixty-six completed data pairs with T1 and T2 pre-injury data were available. Mean pre-injury EQ-5D summary scores were 0.906 (T1) and 0.905 (T2), respectively, with moderate intertemporal agreement (intraclass correlation coefficient (ICC) T1T2 = 0.595). In absolute terms, 442 (37.9%) respondents reported a different pre-injury EQ-5D profile at T2 compared to T1. The least stable EQ-5D dimension was pain/discomfort (20.2% reported a change). Mean T2 pre-injury EQ-VAS score was significantly higher than mean T1 pre-injury EQ-VAS score (T2 84.6 versus T1 83.3). Multivariable logistic regression analysis indicated that lower educational level, comorbid disease and having PTSD symptoms were independent predictors of change of pre-injury EQ-5D profile. CONCLUSIONS: Despite one third of respondents reported a different pre-injury health level, if asked for on two interview occasions separated by 1 year, on the group level this difference was nil (EQ-5D summary score) to small (EQ-VAS). The consistent symmetrical pattern of change suggests random error to play the largest role. Intertemporal reliability was the same in EQ-5D profiles vs. EQ-VAS scores, ruling out scale effects. Particularly certain trauma subgroups showed highest distortion. While group comparisons may be trusted, in pre-post analysis and repeated measure analysis the individual injury impact and recovery pattern may be wrongly estimated.